Endovascular management of early-onset post-nephrectomy renal arteriovenous fistula: A report of two cases. (24th December 2015) - Yin, Henghui; Zhao, Yang; Wang, Mian; Wang, Shenming; Chang, Guangqi
Purpose: Here, we report two cases of early-onset post-nephrectomy renal arteriovenous fistula who were successfully managed by implantation of patent ductus arteriosus occluders. Case report: Both patients were female, aged 38 and 36 years. They received left renal nephrectomy 9 and 6 months, respectively, with a complaint of chest congestion and dyspnea before admitting to our center. Computed tomographic angiography revealed a huge arteriovenous fistula of the left renal pedicle with a renal venous aneurysm in both patients. The fistulas were isolated by implanting patent ductus arteriosus occluders in the renal artery stumps. Clinical symptoms disappeared after intervention. Computed tomographic angiography confirmed the effectiveness of the occluders during follow-up time. The venous aneurysms shrank to normal size. Conclusion: Our experience indicates that post-nephrectomy renal arteriovenous fistula can present as an early complication which can be efficiently managed by endovascular occlusion of the arterial stump by patent ductus arteriosus occluder.